In the name of human rights: the problematics of EU ethical foreign policy in Africa and elsewhere - Rutazibwa, Olivia Umurerwa (Afrika Focus, 2014)
This doctoral research project explores avenues to research ethically defined foreign policy differently, i.e. in ways that more systematically account for its counterproductive elements. Building on the specific case of the European Union’s foreign policy in sub-Saharan Africa, embodied by the 2000 Cotonou Agreement and the 2007 Joint Africa-EU Strategy, through four papers and one books review, the study firstly develops the Ethical Intervener Europe analytical framework to account for the embedded problematics in the EU’s ethical foreign policy. Secondly, through an eclectic theoretical approach, the study seeks to theoretically pin-point some alternatives to think about ethical foreign policy and finally, looks to concretize it through its application on the case of relative autonomous peace- and state-building in Somaliland. This research report briefly introduces the different findings and addresses the need for further research in view of a decolonial approach to the study of ethical foreign policy in a context of structural inequality. Key words: ethical foreign policy, (humanitarian) interventions, EU, sub-Saharan Africa, Somaliland, decoloniality, democratization, state-building